Paradoxical embolism as a cause of ischemic cerebrovascular disease in a young female - Carrasco-Lozano, Luis Enrique (2021)
This is the case of a 44-year-old female patient with no risk factors, extensive stroke and deep vein thrombosis. Transesophageal echocardiography showed the presence of a permeable oval foramen, which allowed a paradoxical embolism to be raised as a cause of ischemic cerebrovascular event. Otherprobable etiologies were discarded. The patient was discharged with clinical improvement receiving anticoagulation, physical therapy and rehabilitation.